(NpODNQTAQ CELINA(B: {(NrOMAN(B];s (NsUDXBA ^ELOWEKA(B: [(NrASSKAZ(B] /s - (N{OLOHOW(B, (NmIHAILs ((NmOSKWA(B:s (NhUDOVESTWENNAQ LITERATURA(B,s, 1978)
(Nw KNIGU WHODIT ROMAN m(B.(Na(B. (N{OLOHOWA (B"(NpODNQTAQ CELINA(B", (NZAPE^ATLEW[IJ \POHU KOLLEKTIWIZACII(B, (NKRU[ENIE STARYH I ROVDENIE NOWYH FORM VIZNI(B, (NI RASSKAZA (B"(NsUDXBA ^ELOWEKA(B" - (NO WELI^II(B, (NSILE(B, (NKRASOTE DU[I OBYKNOWENNOGO RUSSKOGO SOLDATA(B.s
rus
Keywords: (NpOWESTI I RASSKAZYs; (NiSTORI^ESKIJ ROMANs; (NsOWETSKAQ LITERATURAs